Catestatin Prevents Macrophage-Driven Atherosclerosis but Not Arterial Injury–Induced Neointimal Hyperplasia - Kojima, Miho; Ozawa, Nana; Mori, Yusaku; Takahashi, Yui; Watanabe-Kominato, Kaho; Shirai, Remina; Watanabe, Rena; Sato, Kengo; Matsuyama, Taka-aki; Ishibashi-Ueda, Hatsue; Koba, Shinji; Kobayashi, Youichi; Hirano, Tsutomu; Watanabe, Takuya (Thrombosis and Haemostasis, 2018)
Catestatin, a catecholamine-release inhibitory peptide, has multiple cardiovascular activities. Conflicting results have been recently reported by increased or decreased plasma levels of catestatin in patients with coronary artery disease (CAD). However, there have been no previous reports regarding the effects of catestatin on arteriosclerosis. This study evaluated the vasoprotective effects of catestatin on human macrophages, human aortic smooth muscle cells (HASMCs) and human umbilical vein endothelial cells (HUVECs) in vitro, and aortic atherosclerosis and wire injury-induced femoral artery neointimal hyperplasia in apolipoprotein E–deficient (ApoE−/−) mice fed with a high-cholesterol diet. Histological expression of catestatin in coronary artery lesions and its plasma level were compared between CAD and non-CAD patients. Catestatin was abundantly expressed in cultured human monocytes, macrophages, HASMCs and HUVECs. Catestatin significantly suppressed lipopolysaccharide-induced upregulation of tumour necrosis factor-α, vascular cell adhesion molecule-1 and intercellular adhesion molecule-1 in HUVECs. Catestatin significantly suppressed inflammatory responses and oxidized low-density lipoprotein-induced foam cell formation associated with acyl-CoA:cholesterol acyltransferase-1 downregulation and ATP-binding cassette transporter A1 upregulation in human macrophages. Catestatin significantly suppressed migration, proliferation and collagen-1 expression without inducing apoptosis, and increased elastin and fibronectin expression in HASMCs. Administration of catestatin into ApoE−/− mice significantly retarded entire aortic atherosclerotic lesions with declined contents of macrophages, SMCs and collagen fibres in atheromatous plaques, but not the femoral artery injury–induced neointimal hyperplasia. In CAD patients, catestatin levels were significantly decreased in plasma but increased in coronary atheromatous plaques. This study provided the first evidence that catestatin could prevent macrophage-driven atherosclerosis, but not SMC-derived neointimal hyperplasia after vascular injury.
Keywords: catestatin; atherosclerosis; restenosis; macrophage; smooth muscle